Monitoring, suppression and molecular regulation mechanisms of mycotoxin-producing fungi - Abbas, Asmaa Shaaban Abdo (fi=Turun yliopisto|en=University of Turku|, 2024)
Within the group of filamentous fungi, Aspergillus flavus is a prominent species because of its capability to produce aflatoxin B1 (AFB1). The consumption of AFB1-contaminated food and feed causes aflatoxicosis, which can lead to serious health risks, particularly liver damage, primary liver cancer, and even death. Research has indicated that over 5 billion people worldwide are exposed to aflatoxins (AFs) through their diet, contributing to an annual occurrence of up to 155,000 cases of liver cancers. Therefore, AFs have been classified as group 1 carcinogens by the International Agency for Research on Cancer. Many countries have set limits for the AFB1 occurrence in food and feed, with more than 75 countries imposing a maximum limit of 5 µg/kg in food products. To comply with food safety regulations and official standards, precise and sensitive analytical techniques for detecting AFB1 are required. Aflatoxin biosynthesis pathway consists of 30 genes and includes transcriptional regulators aflR and aflS. AflR is a master regulator protein and is essential for the AFB1 production, in contrast, the precise role of AflS as aflatoxin regulator remains unclear. Owing to the adverse effects of AFB1 on human and animal health, the prevention of AFB1 accumulation in food and feed is necessary. Plant-derived compounds are promising biocontrol agents to inhibit the production of aflatoxin by A. flavus and deoxynivalenol (DON) by Fusarium graminearum fungi. My doctoral research had three primary objectives. First, I aimed to develop new methods to identify aflatoxigenic Aspergillus strains and detect aflatoxin contamination in food. I applied a polyphasic approach, integrating data from phylogenetic, sequence, and toxin analyses, to the Aspergillus isolates. This enabled to identify the key genomic characteristics, genetic diversity and phylogenetic relationships among the Aspergillus isolates. We then developed a new and rapid noncompetitive immunoassay for AFB1 detection in food. This assay utilized a monoclonal capture antibody and a unique anti-immunocomplex (anti-IC) antibody fragment (scFv) derived from a synthetic antibody library. The single-step assay is fast, performed in 15 min, and has a detection limit of 70 pg/mL for AFB1. Second, I investigated the molecular mechanisms governing the DNA binding activity of AflR, and examined how AflS modulates it. Biophysical data confirmed that AflR and AflS directly interact forming a protein complex. AflS was found to moderately reduce the binding affinity of AflR to its target DNA site. Kinetic assays additionally suggested that two AflR monomers sequentially bound to the palindromic target DNA sequence forming the stable AflR-DNA complex. Third, I investigated and found that antioxidant-rich methanolic extract from Zanthoxylum bungeanum (Z. bungeanum) plant inhibited the growth and toxin production of Aspergillus and Fusarium fungi. Transcriptomic analysis indicated that the extract indeed repressed the AFB1 biosynthesis pathway in A. flavus and additionally generated significant transcriptional changes in several other secondary metabolite pathways. The effects were apparently mediated by the global regulators of secondary metabolism and cell development, including the velvet complex, instead of pathway specific regulators (AflR and AflS). Furthermore, co-inoculating the extract with F. graminearum effectively inhibited the fungal growth and DON production in both laboratory and field conditions. Taken together, these findings highlight the importance of distinguishing aflatoxin and non-aflatoxin producing fungi, as well as understanding the molecular interactions between the master transcription regulators AflR, AflS, and their DNA binding activities. Additionally, the findings suggest that Z. bungeanum extracts may facilitate the development of effective strategies to control AFB1 and DON contaminations.